Microbiome analysis of Brazilian women cervix reveals specific bacterial abundance correlation to RIG-like receptor gene expression - Britto, Alan Messala A.; Siqueira, Juliana D.; Curty, Gislaine; Goes, Livia R.; Policarpo, Cintia; Meyrelles, Angela R.; Furtado, Yara; Almeida, Gutemberg; Giannini, Ana Lucia M.; Machado, Elizabeth S.; Soares, Marcelo A. (Frontiers in Immunology, 2023)
The relationship between microbiome, immunity and cervical cancer has been targeted by several studies, yet many questions still need to be elucidated. We characterized herein the virome and bacteriome from cervical samples and correlated these findings with innate immunity gene expression in a Brazilian convenience sample of HPV-infected (HPV+) and uninfected (HPV-) women. For this purpose, innate immune gene expression data were correlated to metagenomic information. Correlation analysis showed that interferon (IFN) is able to differentially modulate pattern recognition receptors (PRRs) expression based on HPV status. Virome analysis indicated that HPV infection correlates to the presence of Anellovirus (AV) and seven complete HPV genomes were assembled, including one genome of HPV51 with a novel 30-nucleotide deletion in E2. Bacteriome results unveiled that vaginal community state types (CST) distribution was independent of HPV or AV status, although bacterial phyla distribution differed between groups. Furthermore, TLR3 and IFNαR2 levels were higher in the Lactobacillus no iners-dominated mucosa and we detected correlations among RIG-like receptors (RLR) associated genes and abundance of specific anaerobic bacteria. Collectively, our data show an intriguing connection between HPV and AV infections that could foster cervical cancer development. Besides that, TLR3 and IFNαR2 seem to create a protective milieu in healthy cervical mucosa (L. no inners-dominated), and the correlation between RLRs, well known viral RNA receptors, and anaerobic bacteria, pointing out to RLRs implication in dysbiosis.